2010
DOI: 10.1161/circulationaha.109.889725
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and Functional Characterization of a Novel Cardiac-Specific Human Tropomyosin Isoform

Abstract: Background-Tropomyosin (TM), an essential actin-binding protein, is central to the control of calcium-regulated striated muscle contraction. Although TPM1␣ (also called ␣-TM) is the predominant TM isoform in human hearts, the precise TM isoform composition remains unclear. Methods and Results-In this study, we quantified for the first time the levels of striated muscle TM isoforms in human heart, including a novel isoform called TPM1. By developing a TPM1-specific antibody, we found that the TPM1 protein is ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
129
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 81 publications
(145 citation statements)
references
References 39 publications
1
129
0
Order By: Relevance
“…It has been shown that transcriptional loss of TPM1 in hearts results in cardiomyopathy. 27,47 Our findings indicate that posttranscriptional loss of TPM1 in arteries may contribute to ASO.…”
Section: Wang Et Almentioning
confidence: 68%
See 2 more Smart Citations
“…It has been shown that transcriptional loss of TPM1 in hearts results in cardiomyopathy. 27,47 Our findings indicate that posttranscriptional loss of TPM1 in arteries may contribute to ASO.…”
Section: Wang Et Almentioning
confidence: 68%
“…It has been shown that transcriptional loss of TPM1 in hearts results in cardiomyopathy. 27,47 Our findings indicate that posttranscriptional loss of TPM1 in arteries may contribute to ASO.TPM1 expression occurs later than that of SM ␣-actin and smooth muscle myosin heavy chain in smooth muscle cell development, and it has been suggested to be a better phenotypic marker for quiescent smooth muscle cells. 48 In the present study, we found that both TPM1 and SM ␣-actin were abundantly expressed in normal arteries.…”
mentioning
confidence: 81%
See 1 more Smart Citation
“…Echocardiographic and Pressure Overload MeasurementsEchocardiographic measurements were performed utilizing a 30-MHz high resolution transducer (Vevo 770 high resolution imaging system) after anesthetization of 3-month-old mice as previously described (24). Echocardiographic dimensions and thicknesses were taken from two-dimensional guided M-Mode from the parasternal long axis view in triplicate on NTG and TG 12-16-week-old mice.…”
Section: Methodsmentioning
confidence: 99%
“…HR was also monitored continuously. Transthoracic echocardiographic recordings were then obtained using a 30-MHz high resolution transducer and an integrated rail system (Vevo 770 High-Resolution Imaging System; Visualsonics, Toronto, ON, Canada) as previously described (48).…”
Section: Transthoracic Echocardiographymentioning
confidence: 99%